Effects of breeding chronology on white‐tailed deer productivity in Alabama - Mark A. Turner; William D. Gulsby; Stephen S. Ditchkoff; William N. Gray II; Christopher W. Cook (Wildlife Society Bulletin, 2019)
ABSTRACT Following declines in white‐tailed deer (Odocoileus virginianus) populations during the 19th century, many areas throughout the southeastern United States were restocked from various sources. As a result, some populations remain genetically distinct, and phenotypic traits of source populations, including breeding chronology, have been conserved. For example, average conception dates vary by ≥60 days between populations within some Alabama, USA, counties. Although deer have achieved and maintained sustainable densities across much of the southeastern United States for several decades, it is unclear whether this restocking legacy has demographic consequences relevant to management. Therefore, we analyzed a data set containing information on 270 yearling (1.5 yr old) and 2,116 adult (≥2.5 yr old) female deer collected during 1995–2017 to determine potential effects of breeding chronology on in utero productivity. Parameter estimates from a generalized linear mixed model indicated yearling productivity decreased approximately 16% (95% CL = 0–29%) for each 30‐day increase in mean site‐specific parturition date. We did not observe a similar relationship for adults. We believe the relationships we observed for yearlings may result from an interaction between parturition and plant phenology. Specifically, on sites with relatively late parturition dates, fawns are born near the end of the growing season when suboptimal nutritional conditions may negatively affect productivity during their first year of life. Variation in reproductive output of large ungulates is primarily driven by young females, so managers should be aware that productivity of late‐breeding deer populations may be less than average, especially if those populations are behaving in a density‐dependent manner. In addition, these findings emphasize the importance of considering the potential demographic implications of wildlife translocations resulting from differences in timing of life‐history traits. © 2019 The Wildlife Society.